2011
DOI: 10.1002/hup.1199
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and functional outcomes in patients with major depressive disorder and painful physical symptoms switched to treatment with duloxetine

Abstract: Functional improvement at 8 weeks was positively correlated with mood, pain, and anxiety in patients with major depressive disorder switched to duloxetine. Change in mood and pain exerted a relatively stronger joint effect on functioning than did anxiety in this patient population. Copyright © 2011 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 28 publications
2
11
0
Order By: Relevance
“…To our knowledge, most of the previous studies used symptom severity as outcome measure, 16,[33][34][35][36] whereas only a few studies measured functional outcome. 45 In addition, using continuous variables (ie, HAMD-17 score and MWSAS score) as outcome measures is more precise than using dichotomized outcomes (eg, response/nonresponse or remission/nonremission). 33,36,46 Categorizations of continuous variables may result in loss of power.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, most of the previous studies used symptom severity as outcome measure, 16,[33][34][35][36] whereas only a few studies measured functional outcome. 45 In addition, using continuous variables (ie, HAMD-17 score and MWSAS score) as outcome measures is more precise than using dichotomized outcomes (eg, response/nonresponse or remission/nonremission). 33,36,46 Categorizations of continuous variables may result in loss of power.…”
Section: Discussionmentioning
confidence: 99%
“…Investigators concluded that continuation of an index AD offers inferior 31 may be used to suggest that patients who do not improve may benefit from a treatment switch that occurs earlier than usual; notwithstanding, other studies have failed to confirm this finding. 32,33 Further, it remains unclear whether the improvement observed resulted from a switch from an SSRI to a serotonin and norepinephrine reuptake inhibitor, or if switching to an alternative medication of the same class (for example, SSRIs) would have yielded similar benefits.…”
Section: What Is the Optimal Trial Duration With Ads?mentioning
confidence: 99%
“…6 Functional impairment in patients with MDD seems to improve with treatment along with reduction in depressive symptoms. 7,8 However, functional recovery may lag behind symptomatic remission, [9][10][11] and residual symptoms of depression can delay full functional recovery even in patients who have achieved clinical remission. 12 Treatment goals for patients with MDD, therefore, should include both symptom remission and functional recovery.…”
Section: Introductionmentioning
confidence: 99%